The representations of the prisoner in Carandiru Station - Pedroso, Márcia (2010)
The prison house of São Paulo – known after the neighborhood where it was located, the Carandiru – was the largest prison complex of Latin America. In October 02, 1992, the prison house was subject of the tragic event that went to be known globally as the “Carandiru Massacre”. Due to the undeniable exposition of human misery, in December 08, 1992, part of the Carandiru Complex was destroyed after its progressive deactivation. In 1999, Drauzio Varella wrote a book, “Estação Carandiru” (Carandiru Station), presenting his 12 years of experience as a medical doctor in the prison house. The objective of this paper is to discuss the ideas presented in the book of Varella as possible legitimizing representations of the prison system. The study aims at understanding the content of the book, assuming it as one of the crucial elements in the history of the São Paulo prison house, giving emphasis to its visibility and, at the same time, diffusing ideological fallacies about the prison and its inmates.